Pengaruh Kebijakan Olahraga Boxing Tingkat Nasional terhadap Prestasi Atlet Indonesia (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze the impact of national boxing sports policies on the performance of athletes in Indonesia. Through a qualitative approach with a literature review, this research identifies the challenges and opportunities faced by boxing, including the lack of training facilities, limited amateur competitions, and suboptimal application of sports science. The study also explores the crucial role of the government and private sector in supporting the development of boxing through the organization of internationally recognized championships, such as the Holywings Sports Show (HSS). The analysis results indicate that structured policies and collaborative support between the government and private sectors are essential to enhance the performance of Indonesian boxing athletes on both national and international stages.